Reacting Laminar flow with Applied Magnetic Field in a Channel filled with Saturated Porous Media - Ogunsola, A.W. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this work, we examined reacting laminar flow of a third grade fluid in a channel filled with saturated porous media under the effect of applied magnetic field and variable thermal conductivity. It is assumed that the fluid has temperature-dependent viscosity and reacts satisfying Arrhenius law. We employed Galerkin weighted residual method to solve the resulting non-linear equations. The results show the effects of variable viscosity parameter, Brinkman number, Reynolds number, Prandtl number, Darcy number, Hartmann number and parameter on the flow system.